2000
DOI: 10.1007/s001250050050
|View full text |Cite
|
Sign up to set email alerts
|

Natural variants of human p85α phosphoinositide 3-kinase in severe insulin resistance: a novel variant with impaired insulin-stimulated lipid kinase activity

Abstract: Severe insulin resistance is found in a heterogeneous group of uncommon disorders characterised by acanthosis nigricans, impaired glucose tolerance or diabetes mellitus and in women, features of hyperandrogenism such as oligomenorrhoea and hirsutism [1±3]. The mechanisms underlying severe insulin resistance in human disease remain poorly understood, but mutations in the insulin receptor gene or autoantibodies to the insulin receptor are responsible in only a small minority of cases [4±6]. The increasing knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 50 publications
2
25
2
Order By: Relevance
“…PI 3-kinases catalyze the transfer of phosphate to the 3Ј-OH position of inositol lipids to produce phosphatidylinositol-3,4-bisphosphate and phosphatidylinositol-3,4,5-trisphosphate (PIP 3 ), which in turn act as second messengers by recruiting proteins containing pleckstrin homology (PH) domains to the plasma membrane to assemble signaling complexes (44). In addition to the lipid kinase activity, in vitro experiments have demonstrated that class I PI 3-kinases possess an intrinsic protein serine kinase activity (9,15,40,42).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…PI 3-kinases catalyze the transfer of phosphate to the 3Ј-OH position of inositol lipids to produce phosphatidylinositol-3,4-bisphosphate and phosphatidylinositol-3,4,5-trisphosphate (PIP 3 ), which in turn act as second messengers by recruiting proteins containing pleckstrin homology (PH) domains to the plasma membrane to assemble signaling complexes (44). In addition to the lipid kinase activity, in vitro experiments have demonstrated that class I PI 3-kinases possess an intrinsic protein serine kinase activity (9,15,40,42).…”
mentioning
confidence: 99%
“…In the case of p110␣, this interaction has been shown to increase the lipid kinase activity above that caused by binding of the regulatory subunit to phosphotyrosine. With respect to the negative regulation of the PI 3-kinase activity, it has been reported that the p85 C-terminal SH2 domain binds to the enzymatic product PIP 3 . PIP 3 binding and tyrosine-phosphorylated peptide binding in the SH2 C-terminal domain have been shown to be mutually exclusive (32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Swedish males after 20 years of follow-up from the age of 50 years to the age of 70 years. In vitro the Met326 and Ile326 variants of p85␣ have been shown to have similar basal binding and recruitment to phosphotyrosine-containing immunoprecipitates after insulin stimulation when coexpressed with the catalytic subunit p110␣ in HEK293 cells (14); the catalytic activities of the Met326-or Ile326-containing phosphotyrosine complexes were identical (14).…”
mentioning
confidence: 99%
“…Described in present study results provide the first evidence for association of SNPs in UTRs of INSR and PIKR1 genes with genes expression rates. So far, all investigated in these genes SNPs were localized mainly in coding regions (Kusari et al, 1991;Baynes et al, 2000;Almind et al, 2002;Jamshidi et al, 2006;Højlund et al, 2006). Presented results stand for the first report where evaluation of SNPs in UTRs of INSR and PIK3R1 genes with gene expression levels was performed in peripheral lymphocytes and adipose tissues.…”
Section: Discussionmentioning
confidence: 91%